Pembentukan Karakter Generasi Alpha dalam Dunia Pendidikan di SD Negeri Taraban 06 - Ari Fajar Isbakhi; Widiyatmoko Widiyatmoko; Wahyu Isnaeni (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
In essence, technology has become an inseparable part of Generation Alpha’s life. However, the improper use of technology can affect their overall development. The technology available today has a significant influence on the progress of a nation; therefore, the roles of parents and educators are crucial in encouraging, controlling, and supervising children to prevent technology addiction. When used appropriately, technology can broaden knowledge through the internet and digital devices, enhance creativity in developing skills, and facilitate the learning process. Nevertheless, modern technology can also bring negative impacts, such as dependency, excessive screen time, and reduced social interaction, as children tend to spend more time in front of screens rather than engaging with their surroundings. The purpose of this study is to analyze the influence of technology on Generation Alpha from an Islamic perspective and to explore ways to implement this understanding.(Ari Fajar Isbakhi et al., 2025, p. 287) The research employs a qualitative method with a library research approach. Generation Alpha is a generation that grows up amid rapid, interactive, and dynamic digital technological advancements. This condition presents both opportunities and challenges for the world of education, particularly in shaping students’ character within the school environment. This study aims to analyze the strategies, challenges, and roles of schools in developing the character of Generation Alpha to become intelligent, ethical, and empathetic individuals. The research employs a qualitative descriptive approach through a literature study method. The findings indicate that character education in schools needs to be designed contextually, collaboratively, and technology-based to foster an adaptive Generation Alpha while maintaining strong moral and social values.